The China Challenge : Contending Discourses on International Order - Ho, Benjamin (2018)
Amidst ongoing global debate about how best to engage China is a more fundamental contestation over what kind of international order is emerging in the coming years. To this end, realist, liberal and constructivist assumptions of political behaviour are worth revisiting to make sense of existing political dynamics that shape how states (especially smaller ones) seek to relate with Beijing.